Clinical teaching in applied health science: effects of a student-led journal club on aging and physical activity - Fleiner, Tim; Trumpf, Rieke; Schnorr, Thiemo; Buchner, Theresa; Haussermann, Peter; Zijlstra, Wiebren; Morat, Tobias (BMC medical education, 2023)
Background: This project aims to investigate the effects of a student-led journal club on students’ critical thinking and clinical application skills in the academic field of aging and physical activity. Methods: A pre-post design analysis with data collected in four successive cohorts of the program M.Sc. Sport and Movement Gerontology was conducted. Each student assigned himself/herself to a study, and then led the journal club discussion and published a summary of the journal club via graphical abstract on social media. The students rated their perceived confidence in the beginning (T0) and after the semester (T1) via questionnaire and 5-point Likert scales addressing their ability to review and summarize the evidence, to present it in a journal club and to lead the discussion. Results: 41 students (32 women, M = 25 years SD 1.9 years) were included. The journal club was rated as “very good” (median 2, IQR 1). Students’ confidence on participating, leading the journal club and transferring the results into clinical practice improved significantly (r ≥ 0.6, p < 0.01) – e.g.: “I feel confident in leading a discussion on the literature presented”, T0: “undecided” (median 3, IQR 2) to T1: “rather agree” (median 4, IQR 1, Z= -5.41, r = 0.85, p < 0.01). Discussion: The student-led journal club shows to be an effective teaching approach for the field of aging and physical activity within applied health science education. Especially the students’ self-assignment to the studies and involving the scientific community via social media was rated as useful and highly motivating for students and lecturers.
Online veröffentlicht: 11. Oktober 2023
Gesehen am 03.01.2024